+0

# x 2 -y 2 =55 and x-y=11, then y=

-1
126
2

x2-y2=55 and x-y=11, then y=

Guest May 13, 2017
Sort:

#1
+76827
+2

x ^2 - y^2   =  55

x  -  y  =  11

factor  the first quation

(x + y) ( x - y)  = 55      sub the second equation in for the second factor

(x + y) (11)  =   55        divide both sides by 11

( x + y)   =   5

So......

x - y  =  11

x + y  =  5            add  these  equations

2x  =  16        divide both sides by 2

x  = 8

And using x + y  =  5   means that  y   =   - 3

CPhill  May 13, 2017
#2
-1

x ^2 - y^2   =  55

x  -  y  =  11

factor  the first quation

(x + y) ( x - y)  = 55      sub the second equation in for the second factor

(x + y) (11)  =   55        divide both sides by 11

( x + y)   =   5

So......

x - y  =  11

x + y  =  5            add  these  equations

2x  =  16        divide both sides by 2

x  = 8

And using x + y  =  5   means that  y   =   - 3

LOL>>> ur mom, only ur mom, and nothing but ur mom.

Guest May 13, 2017

### 23 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details